2001
DOI: 10.1103/physrevlett.87.157002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Two Superconducting Gaps inMgB2

Abstract: We have measured the Raman spectra of polycrystalline MgB 2 from 25 cm −1 to 1200 cm −1 . When the temperature was decreased below the superconducting transition temperature T c , we observed a superconductivityinduced redistribution in the electronic Raman continuum. Two pair-breaking peaks appear in the spectra, suggesting the presence of two superconducting gaps. Furthermore, we have analyzed the measured spectra using a quasi twodimensional model in which two s-wave superconducting gaps open on two sheets … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
130
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(143 citation statements)
references
References 22 publications
11
130
1
1
Order By: Relevance
“…50, which compares the fieldinduced variation of κ e at temperatures well below T c for different conventional and unconventional superconductors, amended by our data for MgB 2 at T = 0.60 K. The Nb data 51 reveal the typical salient features of a clean, almost isotropic s-wave superconductor, and confirms the very weak energy transport by quasiparticles far below H c2 , in agreement with Eq. (8). A considerably faster, almost linear in H, increase of κ e is observed for a superconductor with nodes in ∆(k), here exemplified by UPt 3 .…”
Section: Thermal Conductivity In the Mixed Statementioning
confidence: 75%
“…50, which compares the fieldinduced variation of κ e at temperatures well below T c for different conventional and unconventional superconductors, amended by our data for MgB 2 at T = 0.60 K. The Nb data 51 reveal the typical salient features of a clean, almost isotropic s-wave superconductor, and confirms the very weak energy transport by quasiparticles far below H c2 , in agreement with Eq. (8). A considerably faster, almost linear in H, increase of κ e is observed for a superconductor with nodes in ∆(k), here exemplified by UPt 3 .…”
Section: Thermal Conductivity In the Mixed Statementioning
confidence: 75%
“…This two-gap scenario was confirmed experimentally by a number of investigations including heat capacity measurements [126], Raman scattering [127], and tunneling spectroscopy [128]. To understand the pressure effects in superconducting MgB 2 the pinduced changes of the microscopic parameters of the two bands as well as the coupling between the bands need to be taken into account.…”
Section: Pressure Effects In Mgb 2 and Isostructural Intermetallic Comentioning
confidence: 83%
“…1a, the spectrum of the undoped MgB 2 sample is dominated by a band centered around 600 cm −1 , in agreement with previous Raman experiments reporting a band centered between 580 and 630 cm −1 , characterized by a large width (200-300 cm −1 ) and a relevant asymmetry. [8][9][10][11][12] A close inspection of the MgB 2 spectrum of Fig. 1a reveals two weak shoulders on the low-and the high-frequency side of the 600 cm −1 band (ν 2 ), around 400 (ν 1 ) and 750 cm −1 (ν 3 ), respectively.…”
mentioning
confidence: 99%
“…It is quite a general statement that the E 2g mode is expected to allow for the strongest e-ph coupling [5][6][7] and then to play a relevant role in superconductivity. Raman experiments [8][9][10][11][12] carried out on MgB 2 have shown that the spectrum is dominated by a quite large and asymmetric band around 600 cm −1 , ascribed to the E 2g mode. The anomalous width of this phonon peak has been interpreted as a signature of the e-ph coupling.…”
mentioning
confidence: 99%